Leveraging on Sustainable Energy Transition to Change the Energy Narrative of the Dark Continent - Ebhota, Williams S. (International Journal of Energy Economics and Policy, 2021)
This study overviews sustainable development goals (SDGs) and sustainable energy transition (SET) and then examines âˆ’ sub-Sahara Africa's (SSA) participation in SET; challenges of power inadequacy, exploitation, and deployment of zero-carbon based energy; and steps to fast track renewable energy (RE) development and utilisation. The study identifies factors responsible for power inadequacy in the region to include poor power equipment manufacturing infrastructure, pillaging of power projects funds, use of obsolete power facilities, lack of maintenance of power facilities and stations, and abandonment of power facilities due to breakdown. The world's quest to shift from the consumption of fossil fuels to RE has worsened the possibility of SSA overcoming these challenges. The study recognises the management of this shift and modern power attributes, such as decarburisation, digitization, and decentralisation, as to mitigate energy poverty and security, and climate change in the region, as the focus of sustainable energy transition (SET). The study pointed out that the critical steps that are required for socioeconomic growth and to change the negative energy narrative of SSA include âˆ’ RE domestic capacity building; RE policy reforms to support R&D for rapid development; reversed engineering approach; and other steps necessary to improve RE development. Keywords: Renewable energy; sustainable energy transition; SDGs; Dark Continent; CO2 emission; GHG JEL Classification: O13, O14, P18, Q01, Q42 DOI: https://doi.org/10.32479/ijeep.10663